Transcriptional repressor ZEB2 promotes terminal differentiation of CD8+ effector and memory T cell populations during infection - Omilusik, Kyla D.; Best, J. Adam; Yu, Bingfei; Goossens, Steven; Weidemann, Alexander; Nguyen, Jessica V.; Seuntjens, Eve; Stryjewska, Agata; Zweier, Christiane; Roychoudhuri, Rahul; Gattinoni, Luca; Bird, Lynne M.; et al. (Journal of Experimental Medicine, 2015)
ZEB2 is a multi-zinc-finger transcription factor known to play a significant role in early neurogenesis and in epithelial-mesenchymal transition-dependent tumor metastasis. Although the function of ZEB2 in T lymphocytes is unknown, activity of the closely related family member ZEB1 has been implicated in lymphocyte development. Here, we find that ZEB2 expression is up-regulated by activated T cells, specifically in the KLRG1(hi) effector CD8(+) T cell subset. Loss of ZEB2 expression results in a significant loss of antigen-specific CD8(+) T cells after primary and secondary infection with a severe impairment in the generation of the KLRG1(hi) effector memory cell population. We show that ZEB2, which can bind DNA at tandem, consensus E-box sites, regulates gene expression of several E-protein targets and may directly repress Il7r and Il2 in CD8(+) T cells responding to infection. Furthermore, we find that T-bet binds to highly conserved T-box sites in the Zeb2 gene and that T-bet and ZEB2 regulate similar gene expression programs in effector T cells, suggesting that T-bet acts upstream and through regulation of ZEB2. Collectively, we place ZEB2 in a larger transcriptional network that is responsible for the balance between terminal differentiation and formation of memory CD8(+) T cells.
EVALuna2:3800